Paternal and maternal age at pregnancy and autism spectrum disorders in offspring - Luh Putu Rihayani Budi; Mei Neni Sitaresmi; I Gusti Ayu Trisna Windiani (Paediatrica Indonesiana, 2015)
Background The prevalence of autism spectrum disorders (ASDs) has increased 10 times over the past half century, while paternal and maternal age at pregnancy has also increased. Studies looking for an association between paternal or maternal age at pregnancy and ASDs in offspring have not been conclusive. Objective To assess for possible associations between paternal and maternal age at pregnancy and ASDs in offspring. Methods This case-control study had 50 case and 100 control subjects, each case was matched for age and gender to two controls. Case subjects were obtained by consecutive sampling of patients aged 18 months to 7 years who visited the Developmental Behavioral & Community Pediatrics Outpatient Clinic and private growth and development centers from January to April 2013, while control group were children of the same age range and same gender who visited pediatric outpatient clinic at Sanglah Hospital mostly due to acute respiratory tract infection, without ASDs as assessed by the DSM-IV-TR criteria. We interviewed parents to collect the following data: maternal and paternal age at pregnancy, child’s birth weight, history of asphyxia, hospital admission during the neonatal period, pathological labor, maternal smoking during pregnancy, paternal smoking, and gestational age. Data analysis was performed with Chi-square and Fisher’s exact tests. Results Multivariable analysis showed that higher paternal age at pregnancy was associated with ASDs in offspring (OR 6.3; 95%CI 2.0 to 19.3; P 0.001). However, there was no significant association between maternal age during pregnancy and the incidence of ASDs. Asphyxia and paternal smoking were also associated with higher incidence of ASDs in the offspring (OR 10.3; 95%CI 1.9 to 56.5; P 0.007 and OR 3.2; 95%CI 1.5 to 6.9; P 0.003, respectively). Conclusion Paternal age >=40 years increased the risk of ASDs in offspring by 6.3 times. In addition, paternal smoking increased the risk of ASDs in offspring by 3.2 times and asphyxia increased the risk of ASDs in offspring by 10.3 times.